Wind Turbine Asynchronous Generator Control Algorithms. (2015) - Smolin, V.I.; Topolskaya, I.G.
Abstract: The aspects of mass usage of 7-15 meters diameter wind turbines (WT) on 5-15 kW uninterrupted power supply in the continental region conditions at 3-10 m/s dominant wind speeds and 4-6 m/s average annual wind speed is discussed. A method of generating the desired power characteristics of WT, taking into account the differential chart of wind flow distribution and electric energy consumption structure is prposed. We have studied the control algorithms of frequency-controlled asynchronous generator wind turbine to provide the braking of rotor in the modes of partial loading, stabilizing the nominal power and full stop. The approach is illustrated by the analysis of combined mechanical characteristics of the wind turbine and the generator. We discuss the control system of a wind turbine with gain-frequency control of the generator and automatic distribution of generated power between the consumers of self-contained power grid and the static energy storage. We propose the methods of optimization for the generator operating modes based on the of three phase electromechanical converters generalized energy flow theory.